Comparison of High-resolution Anorectal Manometry With Water-perfused Anorectal Manometry - Kang, Hye Ran; Lee, Ji-Eun; Lee, Joon Seong; Lee, Tae Hee; Hong, Su Jin; Kim, Jin Oh; Jeon, Seong Ran; Kim, Hyun Gun (Journal of neurogastroenterology and motility, 2015)
To date, high-resolution manometry has been used mainly in the study of esophageal motility disorders and has been shown to provide more physiological information than conventional manometry, and is easier to interpret. This study aimed to evaluate the usefulness of high-resolution anorectal manometry (HRARM) compared to water-perfused anorectal manometry. Patients who complained of chronic constipation with/without fecal incontinence underwent both water-perfused anorectal manometry and HRARM in a random order on the same day. Resting and squeezing pressures of the anal sphincter, attempted defecation, rectoanal inhibitory reflex, rectoanal contractile reflex, Rao's type of dyssynergia during attempted defecation, anal canal length, defecation dynamic parameters and measurement times for each method were analyzed. Of 14 patients, 7 were female, and the median age was 59 years (range 35-77). Indications for manometry were constipation (n = 8) and constipation with fecal incontinence (n = 6). Resting and squeezing pressures showed that the two methods were strongly correlated (resting pressure: r = 0.746, P = 0.002; squeezing pressure: r = 0.921, P < 0.001). In attempted defection, one equivocal case with water-perfused anorectal manometry was diagnosed type I pelvic floor dyssynergia with HRARM providing detailed pressure changes in internal and external anal spincters, and puborectalis muscle which improved assessment of anorectal disorders. The measurement time for HRARM was significantly shorter than that for water-perfused anorectal manometry (11.3 vs. 23.0 minutes, P < 0.001). Both water-perfused anorectal manometry and HRARM are well tolerated and reliable methods of evaluating defecation disorders of pelvic floor dysfunction. HRARM is likely to provide better physiological information and to require a shorter measurement time compared to water-perfused anorectal manometry.